Using multidimensional scaling and PLS-SEM to assess the relationships between personality traits, problematic internet use, and fear of missing out. Issue 12 (2nd December 2018) - Alt, Dorit; Boniel-Nissim, Meyran
ABSTRACT: Informed by the Compensatory Internet Use theory, this study was aimed at revealing possible links between adults' personality traits, Fear of Missing Out (FoMO), and Problematic Internet Use (PIU). Given the exploratory nature of this study, two statistical techniques were used: Smallest Space Analysis (SSA, a variant of multidimensional scaling), and Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were gathered from 359 adults, by three questionnaires: Fear of Missing Out scale (FoMOs), Short Problematic Internet Use Test (SPIUT), and the Big Five personality trait questionnaire. The SSA results yielded a radex projection. The projection has confirmed the five-factorial theoretical structure of the Big Five personality traits. In the SSA projection, the PIU was found in the extraversion area, the FoMO in the neuroticism area, and both PIU and FoMO factors were in close proximity to each other. Based on the SSA map and the theoretical framework, PLS-SEM was deployed to discover possible links between the research factors. According to the results, the FoMO variable had a mediating role, linking neuroticism to PIU. Limitations, conclusions, and directions for further research are discussed.